2021
DOI: 10.1371/journal.pntd.0009504
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes and metabolic reprogramming during establishment of infection and progression of Trypanosoma brucei brucei through its insect host

Abstract: Trypanosoma brucei ssp., unicellular parasites causing human and animal trypanosomiasis, are transmitted between mammals by tsetse flies. Periodic changes in variant surface glycoproteins (VSG), which form the parasite coat in the mammal, allow them to evade the host immune response. Different isolates of T. brucei show heterogeneity in their repertoires of VSG genes and have single nucleotide polymorphisms and indels that can impact on genome editing. T. brucei brucei EATRO1125 (AnTaR1 serodeme) is an isolate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 87 publications
1
24
0
Order By: Relevance
“…Comparison of the transcriptomes of trypanosomes at the tips and roots of projections showed that migrating cells at the tip expressed high levels of markers for early procyclic forms. This mirrors what is seen in liquid culture 17 , 18 as well as at early time points after flies are infected with stumpy forms 40 . Among the adenylate cyclases differentially expressed between the tip and the root, ACP6 is more highly expressed at the root and is also up-regulated in late procyclic forms.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Comparison of the transcriptomes of trypanosomes at the tips and roots of projections showed that migrating cells at the tip expressed high levels of markers for early procyclic forms. This mirrors what is seen in liquid culture 17 , 18 as well as at early time points after flies are infected with stumpy forms 40 . Among the adenylate cyclases differentially expressed between the tip and the root, ACP6 is more highly expressed at the root and is also up-regulated in late procyclic forms.…”
Section: Discussionsupporting
confidence: 76%
“…The fact that transcripts encoding high-affinity glucose transporters and glycolytic enzymes are not only upregulated in SoMo tips (Fig. 4 ) and in early procyclic forms 17 , but also in trypanosomes at the beginning of a fly infection 40 , is compatible with procyclic forms utilising carbon sources other than proline in tsetse.…”
Section: Discussionmentioning
confidence: 97%
“…Based on both the cluster markers and top genes of each cluster, we were able to assign putative cell-types. C1 and C2 showed expression patterns consistent with midgut procyclics and proventricular forms, respectively, based on known marker genes and bulk transcriptomic data [ 21 , 33 ] ( S2 Table ). C1 was characterized by a single marker gene, FHc (Tb927.3.4500), a fumarate hydratase, which catalyses conversion of fumarate to malate in the TCA cycle ( Fig 1 ) [ 4 , 34 ].…”
Section: Resultsmentioning
confidence: 95%
“…In our experiments we used the EATRO1125 T . brucei strain, which is differentiation-competent but for which an assembled genome [ 64 ] became available only after this work was complete.…”
Section: Resultsmentioning
confidence: 99%